1987
DOI: 10.1007/bf00055376
|View full text |Cite
|
Sign up to set email alerts
|

Tumor hypoxia: its impact on cancer therapy

Abstract: The presence of radiation resistant cells in solid human tumors is believed to be a major reason why radiotherapy fails to eradicate some such neoplasms. The presence of unperfused regions containing hypoxic cells may also contribute to resistance to some chemotherapeutic agents. This paper reviews the evidence that radiation resistant hypoxic cells exist in solid tumors, the assumptions and results of the methods used to detect hypoxic cells, and the causes and nature of tumor hypoxia. Evidence that radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
181
0
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(192 citation statements)
references
References 185 publications
5
181
0
4
Order By: Relevance
“…Hypoxia has been shown to compromise the beneficial effects of chemotherapeutic drugs (Teicher, 1994) and interfere with the response of tumours to radiation (Moulder and Rockwell, 1987). Pretreatment oxygenation levels have been found to be predictive of the radiation response and survival of patients with cancer of the uterine cervix (Hockel et al, 1993;Fyles et al, 1998), head and neck (Gatenby et al, 1988;Nordsmark et al, 1996), oropharyngeal (Aebersold et al, 2001), and early oesophageal cancer (Koukourakis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to compromise the beneficial effects of chemotherapeutic drugs (Teicher, 1994) and interfere with the response of tumours to radiation (Moulder and Rockwell, 1987). Pretreatment oxygenation levels have been found to be predictive of the radiation response and survival of patients with cancer of the uterine cervix (Hockel et al, 1993;Fyles et al, 1998), head and neck (Gatenby et al, 1988;Nordsmark et al, 1996), oropharyngeal (Aebersold et al, 2001), and early oesophageal cancer (Koukourakis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…7 Since the efficacy of radiation therapy hinges on the ability of surrounding normal tissue to tolerate doses of radiation that are cytotoxic to cancer cells, the presence of hypoxic cancer cells severely limits the utility of radiation treatment. 8 Other studies have demonstrated that hypoxic cancer cells are more resistant to chemotherapy than their oxic counterparts. 9,10 The simplest explanation for this phenomenon is distance-cells furthest from blood vessels tend to be exposed to lower drug concentrations.…”
mentioning
confidence: 99%
“…One such difference is that a large proportion of solid tumours contain cells at lower levels of oxygenation than occurs in normal tissues. Such hypoxia in tumours is found in the vast majority of transplanted rodent tumours (Moulder & Rockwell, 1987) and in human tumours xenografts in immunodeficient mice (Rockwell & Moulder, 1990). There is also compelling evidence from a variety of techniques that hypoxic cells are also present in human solid tumours Mueller-Klieser et al, 1981;Vaupel et al, 1991).…”
mentioning
confidence: 99%